2020
DOI: 10.1101/2020.03.02.20030304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased bioefficacy of long-lasting insecticidal nets and the resurgence of malaria in Papua New Guinea

Abstract: Background: Papua New Guinea (PNG) has the highest malaria transmission outside of Africa and long-lasting insecticidal nets (LLIN) are the only vector-control tool distributed country-wide. LLIN were introduced into PNG in about 2005 and have been attributed to have had a huge impact on malaria transmission, with reductions in malaria prevalence observed from 15.7% (2008) to 1% (2014). Since 2015, malaria indicators in PNG have risen significantly. Similar trends have been observed in several African nations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 25 publications
(32 reference statements)
8
35
0
Order By: Relevance
“…[11][12][13] However, decreased bioefficacy of the LLINs distributed between 2013 and 2019 against pyrethroid-susceptible vectors in natural populations in PNG has been observed and is believed to be a factor causing persistent malaria transmission in PNG. 14 Decreased bioefficacy is a result of poor quality of the LLINs and not of physiological or genetic resistance to them. The phenomenon of persistent transmission in the presence of high LLIN coverage in PNG might also be caused by mosquito behaviors such as outdoor and early evening human-biting and opportunistic host selection, which enable mosquitoes to evade the indoor-deployed LLINs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] However, decreased bioefficacy of the LLINs distributed between 2013 and 2019 against pyrethroid-susceptible vectors in natural populations in PNG has been observed and is believed to be a factor causing persistent malaria transmission in PNG. 14 Decreased bioefficacy is a result of poor quality of the LLINs and not of physiological or genetic resistance to them. The phenomenon of persistent transmission in the presence of high LLIN coverage in PNG might also be caused by mosquito behaviors such as outdoor and early evening human-biting and opportunistic host selection, which enable mosquitoes to evade the indoor-deployed LLINs.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, our observations imply that bioefficacy can be manipulated by applying simple procedures. Bioefficacy testing is clearly essential in LLIN quality assurance, especially as we have shown that total AI content may not always be correlated with the ability of a product to kill or knock down mosquitoes 7 . Prequalification procedures and post-market monitoring regulations for LLINs should incorporate this knowledge, ideally by implementing well-validated and standardized methods to measure the surface bioavailable proportion of AI at multiple stages of the product evaluation process, including in recipient countries 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by these novel findings and the notion of heat regeneration, sometimes mentioned in documentation associated with LLIN bioefficacy testing, especially after washing 11 , we performed similar experiments with new and unwashed Permanet 2.0 ® LLINs delivered to PNG in 2019. The LLINs used in this study were the same that exhibited very low bioefficacy in WHO cone bioassays upon arrival in PNG 7 . The purpose of these experiments was to assess whether heating LLINs in a similar way as described by Yang et al for the technical grade AI would increase bioefficacy as measured in WHO standard cone bioassays 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anopheles spp phenotypic resistance to pyrethroids, the insecticides commonly used in LLIN, is not yet present in PNG [10], ruling out a contribution of insecticide resistance to the changes observed in malaria epidemiology. In contrast, decreased bioefficacy of LLINs distributed between 2013 and 2019 has been described [11], as well as behavioural adaptation of local malaria vectors towards more frequent outdoor biting earlier in the evening [12,13]. Lack of use, misuse or repurposing of LLINs may as well be related to the reduced efficacy of this particular malaria control strategy.…”
Section: Introductionmentioning
confidence: 99%